Tobacco use and nicotine dependence among people living with HIV who drink heavily in South Africa: A cross-sectional baseline study - Egbe, C.O.; Londani, M.; Parry, C.D.H.; Myers-Franchi, Bronwyn; Shuper, P.A.; Nkosi, S.; Morojele, N.K. (BMC, 2019)
Background: People living with HIV (PLWH) who drink alcohol and use tobacco are particularly vulnerable to tobacco-induced diseases due to an already compromised immune system. This study investigated the prevalence and factors associated with tobacco use (cigarette and snuff) among PLWH who drink heavily.